Does fiscal policy stimulate economic growth in Ethiopia? ARDL approach - Solomon Tilahun Mengistu (Cogent Economics & Finance, 2022)
In recent years, a vast literature has appeared on the relationship between fiscal policy and long-run economic growth. With the aim to give an overview of the recent discussion and establish a point of departure for future research, this study used time series techniques and rigor empirical model to investigate the link between various components of fiscal policy on Ethiopia's economic growth on annual data for 35 years. It employed the autoregressive distributed lag estimation technique. Results from the bound tests showed that there was a long-run relationship between the variables. Disaggregating government expenditure into productive and unproductive and tax revenue into distortionary and non-distortionary, this study found unproductive expenditure and non-distortionary tax revenue to be neutral to growth as predicted by economic theory. Moreover, productive expenditure has a positive effect on growth while there was evidence of distortionary effects on growth of distortionary taxes. These results give the right signal topolicymakers in Ethiopia in formulating expenditure and tax policies to ensure unproductive expenditures are reduced while at the same time boosting public investment. Furthermore, there is need to encourage private investment in the country.
Keywords: 330; Fiscal policy; time series; economic growth; government expenditure; public investment; private investment